Frontiers in Anti-Infective Drug Discovery: Volume 7 - Atta-ur-Rahman; Iqbal Choudhary, M. (Bentham Science Publishers, 2018)
This book series brings updated reviews to readers interested in advances in the development of anti-infective drug design and discovery. The scope of the book series covers a range of topics including rational drug design and drug discovery, medicinal chemistry, in-silico drug design, combinatorial chemistry, high-throughput screening, drug targets, recent important patents, and structure-activity relationships. Frontiers in Anti-Infective Drug Discovery is a valuable resource for pharmaceutical scientists and post-graduate students seeking updated and critically important information for developing clinical trials and devising research plans in this field. The seventh volume of this series features 7 chapters that cover the following topics: - Gut micriobiota and gastrointestinal cancer - Dengue virus infections - Synergistic antibiotic drug interactions - Molecular modeling of antibacterial drugs - Nucleic acid aptamers as anti-infective agents - Fungal multidrug resistance - The role of hydrogen sulfide in infections